KONTRIBUSI SELF-COMPASSION TERHADAP FEAR OF MISSING OUT PADA PENGGUNA TIKTOK DI KALANGAN GENERASI Z - Anaya Putri, Raisya; Sahrani, Riana (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The phenomenon of fear of missing out (FoMO) is increasingly experienced by Generation Z in line with the rising use of social media, particularly TikTok, which has become a dominant platform with a very high level of engagement. This app, with its algorithm that continuously updates trends and content, can amplify the anxiety of users who feel left out of social activities, leading them to constantly monitor the platform. One psychological factor that can reduce the impact of FoMO is self-compassion, which refers to an individual’s ability to be kind to oneself and accept difficult experiences as part of the human condition. Individuals with higher self-compassion tend to cope better with social pressures and regulate their emotions more effectively. This study aims to examine the role of self-compassion in reducing FoMO among TikTok users in Generation Z. Through analysis of 305 participants aged 18–28 years, the study found that higher levels of self-compassion contribute to a decrease in the tendency to experience FoMO, explaining 13.2% of the variance in FoMO. The findings suggest that self-compassion can be an important factor in reducing the negative impact of FoMO, which is commonly experienced by social media users. These results highlight the importance of developing self-compassion as an adaptive strategy to cope with social pressure in the digital age. ABSTRAK Fenomena fear of missing out (FoMO) semakin banyak dialami oleh Generasi Z seiring dengan meningkatnya penggunaan media sosial, khususnya TikTok, yang telah menjadi aplikasi dominan dengan tingkat keterlibatan yang sangat tinggi. Aplikasi ini, dengan algoritma yang terus memperbarui tren dan konten, dapat meningkatkan rasa cemas pengguna yang merasa tertinggal dari aktivitas sosial yang terjadi, sehingga mendorong mereka untuk terus memantau platform tersebut. Salah satu faktor psikologi yang dapat mengurangi dampak FoMO adalah self-compassion, yaitu kemampuan individu untuk bersikap welas asih terhadap diri sendiri dan menerima pengalaman sulit sebagai bagian dari kehidupan manusia. Individu dengan self-compassion yang tinggi cenderung lebih mampu menghadapi tekanan sosial dan mengelola emosi dengan lebih seimbang. Penelitian ini bertujuan untuk mengkaji peran self-compassion dalam mengurangi FoMO pada pengguna TikTok di kalangan Generasi Z. Melalui analisis terhadap 305 partisipan berusia 18–28 tahun, penelitian ini menemukan bahwa tingkat self-compassion yang lebih tinggi berkontribusi pada penurunan kecenderungan mengalami FoMO, menjelaskan 13,2% variasi FoMO. Temuan ini menunjukkan bahwa self-compassion dapat menjadi faktor penting dalam mengurangi dampak negatif FoMO, yang sering muncul di kalangan pengguna media sosial. Temuan ini menyoroti pentingnya pengembangan self-compassion sebagai strategi adaptif dalam menghadapi tekanan sosial di era digital.